(3QSGdI aj GdUhajIs - (3OGhhO Hf eMehO GdbjUQjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Yjf GdCYjGf HajVI GdCbOS deG habfi Gddg JYGdi hcTa Ydi CfhGQg hQaY Yf Yjf bdHi CcfI CSJGQg s
(3BNQgG (B:s
(3HCi TF ETJZdhG cGfhG ajg HGdceGd hdG ceGd EdG Gddg hMOg gPG BNQ eG CQOfG HjGfg ef GdebOeGJ hGdMeO ddg hMOg GdYRjR s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eMeO CMeO GdeMGei (B_ (3GdHUQI (B(219 (3N(B) s
Keywords: (3GdeLGejYs